analisis metode menghafal mufrodat di PKPBA UIN maulana Maliki Ibrahim Malang: analisis metode menghafal mufrodat di PKPBA UIN maulana Maliki Ibrahim Malang - setiawan, cecef; Fitriani, Laily (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2024)
This research aims to explore and describe information regarding the methods used to support students to enrich their knowledge in learning Arabic. The importance of memorization and its implication of mufrodat is very supportive in the process of learning Arabic, both for beginners and for students who have been learning the language for a long time. The research method used is qualitative field study, data collection techniques using observation and interviews. After consideration and discussion, the results can be determined that the memorization methods used by students at UIN Maulana Maliki Ibrahim Malang are, the Gans-Lern method: memorizing material in its entirety from beginning to end, the Teil Lem method: memorizing part by part and the Vermittlendes method : a combination of both methods. And the use of the Total physical response method. Where students use this method alternately and there are also those who only focus on one memorization method.